Korban Kekerasan Seksual Anak: Bagaimana Keluarga Menjalankan Fungsi Pengasuhannya? - Rahmi Lubis (Asosiasi Psikologi Forensik (Apsifor), 2023)
Sexual violence against children has a detrimental impact on children's physical and psychological health in the short and long term. Sexual violence victims have several risks related to personal and environmental characteristics. The family is the closest factor that should be a protective factor from sexual violence. However, a low social economy can cause children to become victims of these actions. This research aims to describe the family function of child sexual violence victims. Three respondents aged between 9 and 20 years who experienced child sexual violence were involved in interviews and observations after signing informed consent. Interviews using guidelines explored experiences of sexual violence and aspects of family functioning. Research data was analyzed using thematic analysis. The results showed that the three respondents had parents in marital conflicts and attacked each other. Their mother was too busy helping earn a living, so she paid little attention to the respondent's physical and psychological needs. Being physically separated caused the subject not to have emotional closeness with the mother. The mother infrequently communicated with and was violent towards the subject. Parents do not fulfill attention, affection, support, and appreciation. Parents do not socialize enough about life values. There are no strict rules at home and lack of supervision regarding the respondent's activities.